ANALISIS FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PENGENDARA SEPEDA MOTOR: UPAYA MENINGKATKAN KESELAMATAN BERKENDARA - Fadhil, Ammar; Muliani, Fitri; Munandar, Aris (Jurnal Sains Riset, 2024)
Traffic accidents are one of the major challenges faced by many countries, especially in areas with high vehicle density, such as Aceh. Each year, the number of vehicles continues to grow, resulting in thousands of fatalities and many others suffering injuries that significantly affect their quality of life. This study focuses on analyzing one of the factors contributing to traffic accidents among motorcycle riders in Bireuen Regency. Data was collected using a self-reporting method through questionnaires distributed to 250 respondents and analyzed using multiple regression to determine the relationships between variables. The study found that, based on rider perceptions, the "Checking engine condition" indicator from the vehicle factor had the lowest score, below the average of 2.5. Linear regression analysis showed a significance value of 0.05, indicating that all independent variables (X) significantly affect riding safety (Y), with the independent variables contributing 82.6% to safety (R²). The study concluded that human factors, particularly the behavior and attitudes of riders, have the most significant impact. Neglecting these factors leads to decreased safety. However, paying attention to vehicle conditions and road factors while riding can improve safety levels. This is essential to minimizing the risk of traffic accidents for motorcycle riders in Bireuen Regency.